2004
DOI: 10.5194/angeo-22-697-2004
|View full text |Cite
|
Sign up to set email alerts
|

Urban effect on the characteristics of cloud-to-groundlightning over Belo Horizonte-Brazil

Abstract: Abstract. An 8-year climatological analysis (1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996) of lightning network data over Belo Horizonte, a large city located in Southeastern Brazil, and nearby surrounding areas has indicated a significant enhancement of approximately 100% in the negative flash density and of 50% in the positive flash density over and downwind of the city, compared with the other adjacent areas. A decrease of 25% in the percentage of positive flashes was also observed over and downwind of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 13 publications
3
31
0
Order By: Relevance
“…A significant enhancement of approximately 60% and 42% are observed, respectively, for negative and positive flash density over and downwind of the city, compared to the nearby surrounding areas. The percentage increase in the flash density found in this study corresponds well with the results reported by Wescott (1995) and , but it is bit low compared with the results found by Pinto et al (2004). The spatial distribution of the percentage of positive flashes over Seoul and nearby areas has been depicted in Fig.…”
Section: Resultssupporting
confidence: 79%
“…A significant enhancement of approximately 60% and 42% are observed, respectively, for negative and positive flash density over and downwind of the city, compared to the nearby surrounding areas. The percentage increase in the flash density found in this study corresponds well with the results reported by Wescott (1995) and , but it is bit low compared with the results found by Pinto et al (2004). The spatial distribution of the percentage of positive flashes over Seoul and nearby areas has been depicted in Fig.…”
Section: Resultssupporting
confidence: 79%
“…Pinto et al [2004] studied the lightning activity over Belo Horizonte, southeastern Brazil, and nearby surrounding areas. The authors indicated a significant enhancement of approximately 100% in the ÀCG flash density and 50% in the +CG flash density over and downwind of the city, compared with the other adjacent areas.…”
Section: General Physical Properties Of Lightning In Prdmentioning
confidence: 99%
“…Third, also from Fig. 6a, a large spot (the region in white in the state of São Paulo) of high flash density can be seen, coincident with the location of the city of São Paulo, the largest city of the country with a population larger than 10 million people, suggesting that the urban activity is affecting the thunderstorm activity (Naccarato et al, 2003;Pinto et al, 2004;Farias et al, 2008;Bourscheidt et al, 2012). The effects of orography and urban area are not evident in the low-resolution data in Figs.…”
Section: Resultsmentioning
confidence: 86%